2020
DOI: 10.1177/1559325820938543
|View full text |Cite
|
Sign up to set email alerts
|

Protective Effect of Metformin on Sepsis Myocarditis in Zebrafish

Abstract: Purpose: We found in previous study that metformin could treat sepsis myocarditis in a mouse model. We employed the zebrafish model organism to investigate the effect of metformin on sepsis myocarditis. Methods and Results: Wild-type zebrafish was used to establish a sepsis myocarditis model and combined with image software analysis and cytokine detection, the protective dose of metformin was determined. T… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
3
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 31 publications
1
3
0
Order By: Relevance
“…Notably, insulin and metformin readily decreased E. coli counts and showed a better fitted defense barrier to a similar extent as explants pre-exposed to glucose 10 mM. These results agree with the experimental evidence indicating that metformin treatment increases the host resistance to E. coli infection, inhibits its microbial adherence, diminishes its response to chemoattracts and compromises its flagellar motility [ 40 , 100 , 101 ].…”
Section: Discussionsupporting
confidence: 84%
“…Notably, insulin and metformin readily decreased E. coli counts and showed a better fitted defense barrier to a similar extent as explants pre-exposed to glucose 10 mM. These results agree with the experimental evidence indicating that metformin treatment increases the host resistance to E. coli infection, inhibits its microbial adherence, diminishes its response to chemoattracts and compromises its flagellar motility [ 40 , 100 , 101 ].…”
Section: Discussionsupporting
confidence: 84%
“… Inhibiting inflammatory response. [ 50 ] Mice; E. coli Metformin prolonged life span. Promoting the combination of PKCε with IRF4 at mitochondrial microdomain.…”
Section: Introductionmentioning
confidence: 99%
“…Metformin has various cardioprotective properties. Current studies have demonstrated that a protective role of metformin exerts a protective effect against SCM by downregulating the levels of proinflammatory factors, interacting with IRF4 as well as correcting the bioenergetics imbalance [ 61 , 62 ]. Seahorse analysis showed that basal respiration, maximum respiration, spare respiratory capacity, and ATP production were all impaired in response to LPS stimulation, but these effects were ameliorated in the metformin treatment group.…”
Section: Discussionmentioning
confidence: 99%